PENGARUH RATIO LEVERAGE TERHADAP VOLATILITAS SAHAM PADA INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA TAHUN 2004-2008 - Sova, Maya (L2Dikti Wilayah III, 2017)
Leverage ratio is the ratio that indicates the extent to which firms which uses external funds to buy assets to measure the volatility of the stock which is a measure of the uncertainty of stock price movement in the future. The purpose of this study is to analyze the effect of leverage ratio on the volatility of stock on consumer goods industry companies listed in Indonesia Stock Exchange-year period 2004-2008. This research used 19 samples from 33 companies by purposive sampling method, regression analysis with SPSS version 16.00. This study concludes that: (1) the leverage ratio (DER, LT-DER, and DR) has a significant positive and together on the volatility of returns. (2) The decision to invest in Indonesia stock exchange especially in the customer goods industry, in addition to using information leverage ratio of macro factors and other corporate performance must also is analysed.